2021
DOI: 10.1038/s41598-021-97563-2
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and polarization emission properties of a photon-pair source based on a photonic crystal fiber

Abstract: In this work, we experimentally demonstrate a photon-pair source with correlations in the frequency and polarization degrees of freedom. We base our source on the spontaneous four-wave mixing (SFWM) process in a photonic crystal fiber. We show theoretically that the two-photon state is the coherent superposition of up to six distinct SFWM processes, each corresponding to a distinct combination of polarizations for the four waves involved and giving rise to an energy-conserving pair of peaks. Our experimental m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Due to the presence of the two orthogonally polarized fundamental modes in the structure, the SFWM process can occur in various polarization combinations amongst the four fields involved. It can be shown that the SFWM interaction Hamiltonian 61 comprises six different processes related to different polarization combinations of the participating fields, each with a corresponding coefficient 62 . Therefore, the two-photon state is the coherent superposition of the six different polarization combinations.…”
Section: Spontaneous Four-wave Mixing Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the presence of the two orthogonally polarized fundamental modes in the structure, the SFWM process can occur in various polarization combinations amongst the four fields involved. It can be shown that the SFWM interaction Hamiltonian 61 comprises six different processes related to different polarization combinations of the participating fields, each with a corresponding coefficient 62 . Therefore, the two-photon state is the coherent superposition of the six different polarization combinations.…”
Section: Spontaneous Four-wave Mixing Theorymentioning
confidence: 99%
“… List of the SFWM processes related to different polarization combinations of the participating electric fields 62 . p 1 , p 2 , s and i correspond to pump 1 , pump 2 , signal and idler.…”
Section: Spontaneous Four-wave Mixing Theorymentioning
confidence: 99%